Stationary Concepts for Experimental 2x2 Games - Reinhard Selten; Thorsten Chmura (University of Bonn, Bonn Graduate School of Economics (BGSE), 2005)
Four stationary concepts for completely mixed 2x2 games are experimentally compared: Nash equilibrium, quantal response equilibrium, sample-7 equilibrium and impulse balance equilibrium. Experiments on 12 games, 6 constant sum games and 6 non-constant sum games were run with 12 independent subject groups for each constant sum game and 5 independent subject groups for each nonconstant sum game. Each independent subject group consisted of 4 payers 1 and four players 2 interacting anonymously over 200 periods with random matching. The games were selected to yield a reasonably wide distribution over the parameter space. The comparison of the four theories shows that the order of performance from best to worst is as follows: impulse balance equilibrium, sample-7 equilibrium, quantal response equilibrium, Nash equilibrium. The new concepts of sample-7 equilibrium and impulse balance equilibrium are explained in the text.
Keywords: 330